(Invited) Observation of Stress Responses of Bacteria Confined in a MEMS Microfluidic Chip. (14th September 2015) - Nishimura, Yusuke; Ishida, Makoto; Sawada, Kazuaki; Ishii, Hiromu; Machida, Katsuyuki; Masu, Kazuya; Wang, Changle; Iida, Kenichiro; Saito, Mitsumasa; Yoshida, Shinichi
Abstract : This work describes the new and simple method for observing bacterial behavior of stress response such as to light irradiation in a polydimethylsiloxane (PDMS) -based MEMS microfluidic chip. The fluorescence was observed from Legionella cells confined in small spaces among microbeads. Ultraviolet (UV) light irradiation was found to be a trigger for producing fluorescent material. Confining bacteria in the small spaces made by the MEMS technique is an effective way for investigating their stress response.